Mineralogy and upgrading ability of Mejel valley zircon ore - H. Akbari; SH. Shahsavari; M. Noaparast; M. Oliazadeh (Society for Mining, Metallurgy & Exploration, 2005)
Mejel valley zircon ore in Iran is located in north part of Iran and was sampled to evaluate its concentration. The aim of this project was to define the mineralogy of this zone and separating zircon from other minerals using gravity concentrators and magnetic separators. It is constituted of various valuable minerals, mainly zirconium, niobium-tantalum, titanium, rare earth elements particularly cerium-bearing minerals namely zircon, sphene and rare earth elements oxides. We used statistical method for designing of experiments. Yates method used for analysis of basic experiments results. The grade of zircon in primary sample was 1.1%. Different experiments were designed to optimize all required parameters. The final concentration with 75% zircon was produced and final recovery was 79%. Finally, lab-scale based flow sheet was prepared using experiments results.